Altered type 1 interferon responses in alloimmunized and nonalloimmunized patients with sickle cell disease. Issue 4 (27th July 2021) - Madany, Emaan; Lee, June; Halprin, Chelsea; Seo, Jina; Baca, Nicole; Majlessipour, Fataneh; Hendrickson, Jeanne E.; Pepkowitz, Samuel H.; Hayes, Chelsea; Klapper, Ellen; Gibb, David R.
Abstract: Patients with sickle cell disease (SCD) have a high prevalence of RBC alloimmunization. However, underlying mechanisms are poorly understood. Given that proinflammatory type 1 interferons (IFNα/β) and interferon stimulated genes (ISGs) promote alloimmunization in mice, we hypothesized that IFNα/β may contribute to the increased frequency of alloimmunization in patients with SCD. To investigate this, expression of ISGs in blood leukocytes and peripheral blood mononuclear cells (PBMCs) of previously transfused SCD patients with or without alloimmunization and race‐matched healthy controls were quantified, and IFNα/β gene scores were calculated. IFNα/β gene scores of SCD leukocytes and plasma cytokines were elevated, compared to controls (gene score, p < 0.01). Upon stimulation with IFNβ, isolated PBMCs from patients with SCD had elevated ISGs and IFNα/β gene scores ( p < 0.05), compared to stimulated PBMCs from controls. However, IFNβ‐stimulated and unstimulated ISG expression did not significantly differ between alloimmunized and non‐alloimmunized patients. These findings indicate that patients with SCD express an IFNα/β gene signature, and larger studies are needed to fully determine its role in alloimmunization. Further, illustration of altered IFNα/β responses in SCD has potential implications for IFNα/β‐mediated viral immunity, responses to IFNα/β‐based therapies, and other sequelae of SCD.